2014
DOI: 10.3390/molecules19044548
|View full text |Cite
|
Sign up to set email alerts
|

Five Withanolides from the Leaves of Datura metel L. and Their Inhibitory Effects on Nitric Oxide Production

Abstract: Four new withanolides named dmetelins A-D (compounds 1-4), along with the known compound 7α,27-dihydroxy-1-oxo-witha-2,5,24-trienolide (5) were isolated from the leaves of Datura metel L. (Solanaceae). Their structures were elucidated on the basis of detailed analysis of 1D and 2D NMR and mass spectrometry data. All the compounds were evaluated for their inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells. Compounds 1, 4 and 5 showed significant inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Dmetelins A-D, and 7α,27-dihydroxy-1-oxo-witha-2,5,24-trienolide isolated from the leaves of Datura metel were evaluated for their inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells. Compounds, dmetelin A, D and 7α,27-dihydroxy-1-oxo-witha-2,5,24-trienolide, showed significant inhibitory activities, and compounds dmetelin B and C showed moderate inhibitory activities with IC 50 values of 17.8, 11.6, 14.9, 33.3 and 28.6 μM, respectively [84].The aqueous extracts of Datura fastuosa leaves and seeds were evaluated for the analgesic effect on acetic acid-induced writhing and hot plate reaction in mice. The results revealed that Datura fastuosa leaves and seeds extracts at doses of 400 and 800 mg/kg orally induced analgesic effects.…”
Section: Antiinflammatory Analgesic and Antipyretic Effectsmentioning
confidence: 99%
“…Dmetelins A-D, and 7α,27-dihydroxy-1-oxo-witha-2,5,24-trienolide isolated from the leaves of Datura metel were evaluated for their inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells. Compounds, dmetelin A, D and 7α,27-dihydroxy-1-oxo-witha-2,5,24-trienolide, showed significant inhibitory activities, and compounds dmetelin B and C showed moderate inhibitory activities with IC 50 values of 17.8, 11.6, 14.9, 33.3 and 28.6 μM, respectively [84].The aqueous extracts of Datura fastuosa leaves and seeds were evaluated for the analgesic effect on acetic acid-induced writhing and hot plate reaction in mice. The results revealed that Datura fastuosa leaves and seeds extracts at doses of 400 and 800 mg/kg orally induced analgesic effects.…”
Section: Antiinflammatory Analgesic and Antipyretic Effectsmentioning
confidence: 99%
“…The residue was dissolved in 1 mL pyridine and 0.7 mL silylation-derived agent, and added to the solution for shaking for 5 min, then placed at room temperature for 4 h, and 1.5 mL distilled water was added. After centrifugation, the supernatant was detected by gas chromatography (GC) [ 5 , 6 ]. The glycosyl configurations of compounds 1 – 4 were determined by the same retention time ( t R ) of standard d -fructose ( t R = 6.3 min) for compounds 1 – 3 , and d -galactose and d -glucose for compound 4 ( t R = 32.5 min and t R = 16.8 min).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…All the standard substances were isolated and purified by our laboratory [4,5,21,[27][28][29] (Figure 4). UPLC analysis determined that the purity of all target compounds was above 98%.…”
Section: Chemical Reagents Equipment and Standard Solutionsmentioning
confidence: 99%